Extraction and characterization of pectin from dragon fruit (Hylocereus polyrhizus) peel - Mohamad Zahari, Nur Izalin (2013)
The national acreage of dragon fruit production increased yearly, which at the same time generated a great amount of the fruit peel, therefore, this thesis was designed to study the extraction of pectin from dragon fruit peel and to determine the pectin characteristics. Pectin was successfully extracted from dragon fruit peel (DFP) with 30.08% yield at optimum extraction conditions of 67.7 oC for 77 min at pH value of 2.0. The pectin contained 7.81 % moisture, 0.04 % fat, 1.15 % protein, 4.73 % ash and 62.76 % total dietary fibre. The extracted pectin was a heteropolysaccharide which consisted of seven monosaccharides namely galacturonic acid, mannose, rhamnose, galactose, glucose, arabinose and xylose. The total neutral sugar content was 60.95%. Functional groups identification using Fourier transform infrared spectroscopy (FT-IR) and the degree of esterification (DE) derived from FT-IR spectrum confirmed that DFP pectin is a high methoxyl pectin with a DE 62.88%. Molecular weight and polydispersity ratio were determined using high performance size exclusion chromatography with multi angle laser light scattering detector (HPSEC-MALLS). DFP pectin has a molecular weight of 87 kDa with a polydispersity ratio of 8.12 and its estimated root mean square (RMS) radius average was 33 nm. Hunter L*, a*, and b* values of the DFP pectin were 39.95, 34.87 and 20.18, respectively, which showed the light pink color of the extracted pectin. DFP pectin demonstrated non-Newtonion, pseudoplastic characteristic at higher concentrations (2% and 3%) and exhibited several textural characteristics similar to that of citrus and apple pectins. DFP pectin has the highest water holding capacity (5.50 g/g), medium oil holding capacity (1.24 g/g) and swelling capacity (5.50 g/g) when compared to two commercial (citrus and apple) pectins. In addition, DFP pectin demonstrated good emulsifying activity (66.66%), emulsion stability (97.00%), foaming capacity (60.33%) and also foaming stability (64.44%, after 2 hr of foam formation). For application of DFP pectin in pineapple jam, a concentration of 2% of DFP pectin was needed to make the pineapple jam well set. For the sensory characteristics, no significant (p<0.05) differences were observed between the mean scores of the jam produced using DFP and commercial pectins except for the colour attribute. All results suggested that dragon fruit peel had the potential in producing pectin for commercial food industry application. Because of its good hydration properties, DFP pectin might be suitable to be used as thickening, emulsifying, stabilizing and foaming agent in food.